2020
DOI: 10.15452/cejnm.2020.11.0030
|View full text |Cite
|
Sign up to set email alerts
|

Quality of work life among nurses working at a provincial general hospital in Vietnam: a cross-sectional study

Abstract: Aim: To measure the overall level of quality of work life (QWL), and its association with personal and work-related factors among nurses working at a provincial general hospital in Vietnam. Design: A cross-sectional study. Methods: One hundred and sixty nurses were selected by stratified random sampling. Questionnaires were used to survey personal factors, job position, salary, and working years, including work life dimensions. The reliability of the instrument used for the survey was tested using Cronbach alp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Studies have shown that nurses with higher levels of education experience better quality of work life. 3 , 5 , 10 , 21 , 24 , 25 , 31 , 32 This is because it affects their salary, 5 , 10 , 21 job responsibilities, 24 workload, 10 promotion opportunities, 25 and occupational position. 31 However, according to Moradi et al, 34 nurses with lower levels of education reported a better quality of work life than those with higher levels of education.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that nurses with higher levels of education experience better quality of work life. 3 , 5 , 10 , 21 , 24 , 25 , 31 , 32 This is because it affects their salary, 5 , 10 , 21 job responsibilities, 24 workload, 10 promotion opportunities, 25 and occupational position. 31 However, according to Moradi et al, 34 nurses with lower levels of education reported a better quality of work life than those with higher levels of education.…”
Section: Resultsmentioning
confidence: 99%
“…According to Van et al 3 quality of work life (QWL) refers to an employee’s perception and evaluation of their work in the context of their life. QWL extends to encompass an individual’s life, which, in turn, may influence their work experiences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings were nearly similar to other studies, where the QWL scores of nurses were 106.3±19.1. 3,4 The QWL of the nurses was statistically significant with night shifts in the last month, ability to have meals at an appropriate time, an opportunity to spend time with family and friends, conflicts with co-workers and conflicts with doctors (p<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…3 The QWL is a complex variable that is significantly affected by many issues. 4 These include the nature of the work being performed, the working environment, adequate and just compensation, job opportunities, duty discretion, and participation in decision-making processes, job safety, and occupational stress, organizational security in terms of employment and interpersonal relationships, and work-life balance. [5][6][7] All citizens of Bangladesh should have access to both public and private institutions for high-quality, reasonably priced medical care, according to the country's national health care strategy.…”
Section: Introductionmentioning
confidence: 99%